Impact of Postgraduate Student Internships During the COVID-19 Pandemic in China - Zhang, Wenyi; Lu, Xiaozhong; Kang, Derong; Quan, Jiaxin (Frontiers in Psychology, 2022)
To understand the impact of the COVID-19 pandemic on postgraduate students’ internships in China, 911 students from different regions of China were surveyed through online questionnaires. Among the postgraduate students surveyed, 48.51% of which believed that the pandemic had its greatest impact on colleagues interaction, and 59.60% believed that the pandemic had a strong impact on practical skills. In total, 31.8% of postgraduate internship programs were impacted by COVID-19. The proportions of respondents having severe, moderate, and mild anxiety levels were 1.42%, 4.72%, and 15.92%, respectively; and the rates of severe, moderate, and mild depression were 1.64%, 10.86%, and 21.84%, respectively. ANOVA found that major, degree type, and degree of impact of the pandemic on colleague interactions and improved practical abilities all affected postgraduate mental health. The findings suggest that the mental health of postgraduate students should be monitored during a pandemic, and targeted psychological counseling should be offered. Postgraduate internships should be emphasized as to ensure a smooth internship process during a pandemic period. Psychological counseling and assistance should be provided to those whose internships were affected by the pandemic, and programs should be set up to aid postgraduate students in adapting to the new internship and employment conditions brought on by the “new normal” of pandemic prevention and control.